The Role of Non-Formal Education in Strengthening the Digital Capacity of MSMEs through Telkom Indonesia's CSR Program - Soekamto, Restu Widhi; Raharjo, Santoso Tri; Darwis, Rudi Saprudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have significant potential for growth; however, they continue to face various challenges, particularly in digital adaptation. The Corporate Social Responsibility (CSR) program of PT Telkom Indonesia seeks to strengthen the digital capacity of MSMEs through learning processes based on non-formal education methods. This article aims to analyze the role of non-formal education in strengthening the digital capacity of MSMEs through the CSR program of PT Telkom Indonesia, which is implemented through training, mentoring, and the enhancement of digital access. The method used is a descriptive qualitative approach employing a literature study, with documentation as the data collection technique to analyze digitalization efforts in MSME empowerment as part of the CSR program implementation of PT Telkom Indonesia. The findings indicate that training improves human resource capacity, mentoring strengthens business management, legal compliance, and MSME development, while the utilization of digital technology enhances competitiveness and expands market access. The CSR program can thus be understood as a practice of non-formal education that contributes to strengthening the digital capacity of MSMEs.